Microscopical evaluation of neural connectivity between paired stages of Eudiplozoon nipponicum (Monogenea: Diplozoidae) - Zurawski, T H; Mair, G R; Maule, A G; Gelnar, M; Halton, D W (The Journal of parasitology, 2003)
Diplozoidae monogeneans am fish-gill ectoparasites comprising 2 individuals fused in so-called permanent copula. This unique situation occurs when 2 larvae (diporpee) make contact on the host gin, such that their union triggers maturation into an individual adult worm. The present study examined paired stages of Eudiplozoon nipponioun microscopicaily to ascertain whether somatic fusion involves neural connectivity between these 2 heterogenic larvae. Neuronal pathways were demonstrated in whole-mount preparations of the worm, using indirect immunocytochemical techniques interfaced with confocal scanning laser microscopy for peptidergic and serotoninergic innervations and enzyme cytochemical methodology and light microscopy for cholinergic component. Elements of the central nervous systems of paired worms are connected by commissures in the region of fusion so that the 2 systems are in structural continuity. Interindividual connections were mast apparent between corresponding ventral nerve cords. All 3 classes of neuronal mediators were identified throughout both central and peripheral connections of the 2 nervous systems. The anatomical complexity and apparent plasticity of the diplozoon nervous system suggest that it has a pivotal role not only in motility, feeding, and reproductive behavious but also in the events of larval pairing and somatic fusion.
Keywords: Animals; ploštěnci; cholinesterasy; Gills; infekce červy třídy Trematoda; Trematode Infections; Serotonin; kapři; fluorescenční protilátková technika nepřímá; nemoci ryb; serotonin; infestace ektoparazity; Ectoparasitic Infestations; Fish Diseases; nervový systém; Cholinesterases; žábry; Nervous System; Neuropeptides; Carps; neuropeptidy; Platyhelminths; Fluorescent Antibody Technique, Indirect; zvířata; Microscopy, Confocal; konfokální mikroskopie